Peningkatan Keselamatan Jalan Melalui Reflektor di Wilayah Rawan Jurang di Jorong Lubuk Bauak - Nurfarhanah Nurfarhanah; Tiara Amanta Wisesa; Muhammad Ardhanzel; Khintan Bisma Andromeda; Arsi Putri Yakafi; Kasih Cinta Dewi (CV. ITTC INDONESIA, 2025)
Road safety is a crucial aspect in areas with hazardous geographical conditions such as Jorong Lubuk Bauak, Batipuh Baruah District, Tanah Datar Regency, which features winding roads with sharp turns, narrow widths, minimal lighting, and direct adjacency to steep ravines without safety barriers. Through the 2025 Community Service Program (KKN) of Universitas Negeri Padang, an intervention was carried out in the form of road reflector installation to improve visibility and reduce accident potential, particularly at night and during adverse weather conditions. Activities included planning stages, production of reflector poles from PVC materials, and installation at two strategic points identified through field observation and local community input. Post-installation evaluation results showed significant improvements in road user alertness and ease of recognizing road contours and safe boundaries near ravines. This program demonstrates that simple solutions based on appropriate technology such as road reflectors can be effective and economical alternatives in improving traffic safety in areas with limited infrastructure. It is hoped that this activity can be replicated in other high-risk areas in Indonesia as a concrete implementation of sustainable community service programs.